Subnanosecond switching of gigawatt peak power using a silicon avalanche sharpener; Doklady Physics; Vol. 46, № 8 - Lyubutin S. K.; Mesyats G. A. Gennady Andreyevich; Rukin S. N.; Slovikovskii B. G.; Alichkin E. A. (2001, 2001)
В фонде НТБ ТПУ отсутствует